Before Jackie Robinson : The Transcendent Role of Black Sporting Pioneers - Gems, Gerald R. (Book collections on Project MUSE., 2017)
"While the accomplishments and influence of Jack Johnson, Joe Louis, Jesse Owens, Jackie Robinson, and Muhammad Ali are doubtless impressive solely on their merits, these luminaries of the black sporting experience did not emerge spontaneously. Their rise was part of a gradual evolution in social and power relations in American culture between the 1890s and 1940s that included athletes such as jockey Isaac Murphy, barnstorming pilot Bessie Coleman, and golfer Teddy Rhodes. The contributions of these early athletes to our broader collective history, and their heroic confrontations with the entrenched racism of their times, helped bring about the incremental changes that after 1945 allowed for sports to be more fully integrated. Before Jackie Robinson details and analyzes the lives of these lesser-known but important athletes within the broader history of black liberation. These figures not only excelled in their given sports but also transcended class and racial divides in making inroads into popular culture despite the societal restrictions placed on them. They were also among the first athletes to blur the line between athletics, entertainment, and celebrity culture. This volume presents a more nuanced account of early African American athletes' lives and their ongoing struggle for acceptance, relevance, and personal and group identity."--Back cover